The Wiley Blackwell companion to the study of religion - Segal, Robert Alan; Roubekas, Nickolas P. (The Wiley Blackwell companions to religion, 2021)
Cover -- Title Page -- Copyright Page -- Contents -- List of Contributors -- About the Editors -- Introduction -- Part I Approaches -- CHAPTER 1 Anthropology of Religion -- Definitions and Perspectives -- The Origins of Religion -- Religious Experience -- Modes of Thought -- Bibliography -- CHAPTER 2 Economics of Religion -- Conclusion -- Bibliography -- CHAPTER 3 Literature and Religion -- Origins of the Approach -- Myth Criticism -- From Theology and Literature to Religion and Literature -- Subversion of the Concepts of "Religion" and "Literature" -- Institutional Developments and Global Spread -- Future Directions -- Bibliography -- CHAPTER 4 Phenomenology of Religion -- What "Phenomenology" Means -- How Phenomenology Generally Proceeds -- Philosophical Phenomenology Provides One of the Theoretical Frames for Religious Phenomenology -- Pre-Husserlian Philosophical Phenomenology -- The Philosophical Understanding of Phenomena -- The Philosophical Understanding of "Phenomenology" -- The Place of Phenomenology Within the Sciences -- Husserlian Phenomenology -- Phenomena in Husserlian Phenomenology -- Consciousness as Object-Constituting -- The Steps in the Husserlian Phenomenological Technique -- A Description of Philosophical Phenomenology -- Phenomenology of religion -- Chantepie's religious phenomenology -- Tiele's religious phenomenology -- Kristensen's religious phenomenology -- Van der Leeuw's religious phenomenology -- A Description of Religious Phenomenology -- Recent Critiques of Phenomenology -- Critiques of philosophical phenomenology -- Critiques of religious phenomenology -- Evaluation of the Criticisms of Philosophical and Religious Phenomenology -- Prospects for the Phenomenology of Religion -- Bibliography -- CHAPTER 5 Philosophy of Religion -- The Meaning of Religious Beliefs and Practices -- Debate about the Coherence of Theism.